2013
DOI: 10.1016/j.vaccine.2013.10.025
|View full text |Cite
|
Sign up to set email alerts
|

A cluster randomised controlled trial of a web based decision aid to support parents’ decisions about their child's Measles Mumps and Rubella (MMR) vaccination

Abstract: HighlightsThe use of decision aids for immunisation decisions is under researched and controversial.Parents receiving a decision aid or a leaflet had reduced decisional conflict for the MMR decision.MMR uptake in the decision aid and control arms achieved levels required for population immunity.Leaflet arm parents were less likely to vaccinate their child.Childhood immunisation decision aids can achieve both informed decision-making and uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 43 publications
3
75
0
Order By: Relevance
“…This work contributes to the emerging literature about vaccine communication with parents and can provide additional evidence to inform MMR vaccine communication approaches and perhaps vaccine communication in general. With growing interest in childhood vaccine decision aids, 49 evidence-based approaches are critical to ensuring effective communication about childhood vaccines. Moreover, this work suggests a pattern of parental focus on the child' s well-being, perhaps to the exclusion of concerns about population health.…”
Section: Discussionmentioning
confidence: 99%
“…This work contributes to the emerging literature about vaccine communication with parents and can provide additional evidence to inform MMR vaccine communication approaches and perhaps vaccine communication in general. With growing interest in childhood vaccine decision aids, 49 evidence-based approaches are critical to ensuring effective communication about childhood vaccines. Moreover, this work suggests a pattern of parental focus on the child' s well-being, perhaps to the exclusion of concerns about population health.…”
Section: Discussionmentioning
confidence: 99%
“…The trial 16 concluded that, of the two interventions, only the decision aid achieved both informed decision making and MMR uptake.…”
Section: Discussionmentioning
confidence: 99%
“…16 A total of 220 first-time parents whose first child was offered the first MMR vaccine dose (aged 3-12 months) received either:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shourie et al conducted a three-arm cluster randomized trial comparing the use of a MMR decision aid, to a MMR informational leaflet, to usual care. 45 Decisional conflict was reduced in both intervention arms; children whose parents were in the leaflet arm were less likely to be vaccinated with MMR (91%) compared with the decision aid (100%) and control (99%) arms (P D 0.017). Wroe et al conducted a prospective interventional trial comparing the impact of a 20 page manual on the benefits and risks of childhood vaccinations to support vaccination decisions (intervention) to a less in depth 19 page leaflet published by the Ministry of Health (control).…”
Section: Interventions Focused On Routine Childhoodmentioning
confidence: 95%